Catalytic microwave assisted pyrolysis of aspen - Moen, Johannes; Yang, Changyan; Zhang, Bo; Lei, Hanwu; Hennessy, Kevin; Wan, Yiqin; Le, Zhiping; Liu, Yuhuan; Chen, Paul; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2010)
The effect of catalysts on the microwave pyrolysis of aspen pellets was studied. A range of chlorides, nitrates and metal-oxides were added at 2% of the aspen mass (air dry aspen pellet weight basis). Chlorides in particular were found to favor liquid yield, especially the yield of water phase residue. Average liquid yield with added chlorides was 41% mass of the total biomass input, compared to 35% mass without catalyst. Metal-oxides were found to favor pyrolysis heavy oil, and thus total oil yield, since the yield of light oils seemed to be fairly constant. Nitrates were found to favor pyrolysis gas production. Pure light oils and light oils blended with diesel were found to be a potential diesel fuel substitute. Keywords: Renewable energy, <span style="line-height: 140%; font-family: